PRACTICAL OPPORTUNITIES TO PREPARING STUDENTS FOR CONSTRUCTIVE ACTIVITIES - Nilufar Mukhammadiyeva (American Journals, 2024)
In this article, in the process of preparing students of higher education institutions for constructive activity, the possibilities of developing a model of person-oriented relations, acquiring methodological tools, understanding, accepting and implementing a humanitarian position have been revealed.
Keywords: Constructive activity, paradigm, conceptual approach, personalized education, social institutions, humanity.